A 20‐year experience of ocular herpes virus detection using immunofluorescence and polymerase chain reaction. (6th March 2018) - Satpathy, Gita; Behera, Himansu S; Sharma, Anjana; Mishra, Abhisek K; Mishra, Deepanshi; Sharma, Namrata; Tandon, Radhika; Agarwal, Tushar; Titiyal, Jeewan S
Abstract : Background: To detect the presence of herpes virus in corneal scrapings/corneal grafts of suspected herpetic keratitis patients attending the outpatient department/casualty of the Dr Rajendra Prasad Centre for Ophthalmic Sciences, All India Institute of Medical Sciences, New Delhi for the past 20 years with immunofluorescence assay and to analyse the efficacy of polymerase chain reaction over immunofluorescence for routine laboratory diagnosis in some of the specimens. Methods: Corneal scrapings and corneal grafts were collected by the ophthalmologists from 1, 926 suspected herpetic keratitis patients between 1996 and 2015, among whom 1, 863 patients were processed with immunofluorescence assay and 302 patients were processed with polymerase chain reaction assay for the detection of herpes virus. Of the 302 patients, clinical specimens from 239 patients were analysed by both polymerase chain reaction and immunofluorescence assay. Results: Of the 1, 863 suspected herpetic keratitis patients diagnosed with immunofluorescence assay, 277 (14.9 per cent) were found positive for herpes simplex virus 1 antigen. Similarly, of the 302 suspected herpetic keratitis patients diagnosed by polymerase chain reaction, 70 (23.2 per cent) were found positive for herpes simplex virus DNA. Of the 239 patients diagnosed by both polymerase chain reaction and immunofluorescence assay, 35 (14.6 per cent) were found positive with immunofluorescence assay, 59 (24.7 per cent) were found positive with polymerase chain reaction, 30 (12.5 per cent) were positive with both immunofluorescence and polymerase chain reaction assay. Conclusion: Efficacy and accuracy of the polymerase chain reaction assay was greater compared to the immunofluorescence assay for detection of herpes virus in corneal scrapings/corneal grafts of suspected herpetic keratitis patients. Although the immunofluorescence assay is a rapid test for the detection of herpes virus in suspected herpetic keratitis patients, a combination of polymerase chain reaction with immunofluorescence assay will provide higher reliable and accurate results.